Outsourcing usług budowlanych w zarządzaniu ryzykiem operacyjnym przedsiębiorstw budownictwa drogowego - Wróbel, Reinhard (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
All companies participating in the market game function under conditions of risk and uncertainty. Risk accompanies all economic decisions and is due to incomplete information and the impossibility of prediction of all possible corollaries such decisions may bring about. A construction company is subject to additional risk that is related to particular characteristics of the realized construction processes. The report presents operation risk and the methods and techniques of management of a road engineering company. The report describes outsourcing of construction services as one of the manners of reduction of the operation risk. The purpose of the report in question is to verify the thesis that commissioning of construction work implies transfer of risk to subcontractors. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 669-681